“Gender”, Foucault and some feminist tensions - Posada Kubissa, Luisa (Estudios de Filosofía, 2015)
It seems quite clear that Foucaultian analyses are of interest to critical-feminist theorization. Notwith- standing, this reflection presents the tensions that are produced in terms of concepts such as “gender” or the feminist subject. These tensions occur when the Foucaultian discourse becomes a paradigm of the aforementioned theorization. By setting off primarily from The Will to Knowledge I will suggest here that this theoretical path could lead the feminist thought to an impasse. An impasse where the theorization about the transformation of the conditions of submission of the female sex, its structure as a revolutionary agent of an emancipating process, and the application of the analytical tools (like the category “gender”) that feminist thought has been developing toward all become unfeasible. To sum up, as Alcoff states, we could be facing the threat of “destroying feminism” itself.